2009
DOI: 10.1088/0031-8949/79/06/065007
|View full text |Cite
|
Sign up to set email alerts
|

A Mössbauer experiment in a rotating system on the second-order Doppler shift: confirmation of the corrected result by Kündig

Abstract: We present the results of a Mössbauer experiment in a rotating system, whose performance was stimulated by our recent findings (2008 Phys. Scr. 77 035302) and which consisted of the fact that a correct processing of Kündig's experimental data on the subject gives an appreciable deviation of a relative energy shift E/E between emission and absorption resonant lines from the standard prediction based on the relativistic dilation of time (that is, E/E = −v 2 /2c 2 to the accuracy c −2 , where v is the tangential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
150
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 53 publications
(176 citation statements)
references
References 8 publications
24
150
1
Order By: Relevance
“…The results have shown that previous analyses missed an important effect of clock synchronization and that the correct general relativistic prevision gives k ≃ 2 3 in perfect agreement with the new experimental results in [2]. Thus, the general relativistic interpretation in this letter shows that the new experimental results of the Mössbauer rotor experiment are a new, strong and independent proof of Einstein general relativity.…”
Section: Conclusion Remarkssupporting
confidence: 79%
See 3 more Smart Citations
“…The results have shown that previous analyses missed an important effect of clock synchronization and that the correct general relativistic prevision gives k ≃ 2 3 in perfect agreement with the new experimental results in [2]. Thus, the general relativistic interpretation in this letter shows that the new experimental results of the Mössbauer rotor experiment are a new, strong and independent proof of Einstein general relativity.…”
Section: Conclusion Remarkssupporting
confidence: 79%
“…In other words, its theoretical absence in the works [1]- [8], [11]- [13] reflected the incorrect comparison of clock rates between a clock at the origin and one at the detector [15]. This generated wrong claims of invalidity of relativity theory and/or some attempts to explain the experimental results through "exotic" effects [1,2,11,12,13] which, instead, must be rejected.…”
Section: Clock Synchronizationmentioning
confidence: 99%
See 2 more Smart Citations
“…[18] occurred and that the value for b should be recalculated to give the corrected result, b cor = 1.19 ± 0.03, which substantially disagrees with SRT. The same experimenters repeated a similar experiment [21] and found b = 1.32 ± 0.06, again in serious disagreement with SRT.…”
Section: Maximal Accelerationmentioning
confidence: 85%